GROWTH AND YIELD OF BELL PEPPER (CAPSICUM ANNUUM VAR. GROSSUM) IN SOILLESS MEDIA UNDER SHADE HOUSE - NAGARAJ,; D. M., NEMICHANDRAPPA,; M., AYYANAGOWDAR,; M. S., SRINIVASAREDDY,; G. V. PATIL, M. G, (The Bioscan, 2015)
The experiment was laid out during 2013, to study the different soilless growing media on growth and yield parameters of bell pepper (Capsicum annuum var. grossum) cv. Indira under shade house. The experiment was laid out in a spilt plot design. The seven different soilless growing media were selected viz., cocopeat, rice husk, sawdust separately as M 1 , M 2 and M 3 treatments and these media mixed with 1:1 proportion of vermicompost on volume basis as M 4 , M 5 and M 6 treatments with sandy loam soil as M 7 (control) with two replications. The different observations on each treatment were taken such as number of days to flowering, number of 50 per cent flowering, plant height, number of branches and yield. The result shows that sandy loam soil was found best growth parameter. The highest yield was found in sandy loam soil (88.62 t ha -1 ) and lowest yield was observed sawdust (62.00 t ha -1 ).